Multiple shoot formation in Gloriosa superba: A rare and endangered Indian medicinal plant - RAVINDRA ADE; MAHENDRA RAI (Nusantara Bioscience, 2011)
Abstract. Ade R, Rai M. 2011. Multiple shoot formation in Gloriosa superba: A rare and endangered Indian medicinal plant. Nusantara Bioscience 3: 68-72. We report in vitro growth of callus and multiple shoots and standardized the culture conditions for Gloriosa superba. The main aim of the present study was to evaluate the effect of different growth media with different hormonal concentrations on callus induction and multiple shoot formation in Gloriosa superba. The results indicated that MS medium supplemented with 2,4-D 4.52 mM and BAP 13.30 mM promoted the formation of the maximum number of shoots compared to IAA, IBA and with Gamborg B5 medium supplemented with kinetin, IBA and BAP were found to be superior.